Establishment of Medial Fates along the Proximodistal Axis of the Drosophila Leg through Direct Activation of dachshund by Distalless. - Giorgianni, M.W.; Mann, R.S. (Developmental Cell, 2011)
The proximodistal (PD) axis of the Drosophila leg is thought to be established by the combined gradients of two secreted morphogens, Wingless (Wg) and Decapentaplegic (Dpp). According to this model, high [Wg+Dpp] activates Distalless (Dll) and represses dachshund (dac) in the distal cells of the leg disc, while intermediate [Wg+Dpp] activates dac in medial tissue. To test this model we identified and characterized a dac cis-regulatory element (dac RE) that recapitulates dac's medial expression domain during leg development. Counter to the gradient model, we find that Wg and Dpp do not act in a graded manner to activate RE. Instead, dac RE is activated directly by Dll and repressed distally by a combination of factors, including the homeodomain protein Bar. Thus, medial leg fates are established via a regulatory cascade in which Wg+Dpp activate Dll and then Dll directly activates dac, with Wg+Dpp as less critical, permissive inputs.